A exposição ao glifosato, durante a prenhez e a lactação, altera o metabolismo lipídico hepático da prole adulta de camundongos machos alimentados com dieta hiperlipídica - Vargas, Rodrigo (2018)
In the present study, we evaluated the effects of maternal exposure to glyphosate, during pregnancy and lactation period, in hepatic lipid metabolism on adult mice offspring with high-fat diet-fed. Thus, female mice C57BL/6 were randomly divided in: 1) Control group (CTL), which received standard chow and pure water ad libitum and 2) Glyphosate group (GF), which received standard chow and water with 0.5% of commercial formulation of GF (Roundup Original DI®). The treatment occurred from day 0 at 30th postnatal day, keeping the same food supplementation. At 60th postnatal day, offspring was separated in four groups: CTL group animals were subdivided in 1a) CTL-DP-F1 group, which kept same food supplementation and 1b) CTL-DH-F1 group, which received high-fat diet; GF group animals were subdivided in 2a) GF-DP-F1 group, which kept the same food supplementation and 2b) GF-DH-F1 group, which received a high-fat diet. At 150 days of life, offspring were euthanized. Body weight gain were similar between CTL-DP-F1 and GF-DP-F1, however lower than high-fat diet-fed groups. Nevertheless, this parameter was significantly lower in GF-DH-F1 groups when compared to CTL-DH-F1. High-fat diet consumption increased fat pad mass in CTL-DH-F1 group in relation to others groups at 150 days of age. GF-DH-F1 group increased 75 and 60% retroperitoneal and perigonadal fat pads, respectively, in relation to CTL-DP-F1 and GF-DP-F1. Interestingly, fat pad accumulation was 50% lower in GF-DH-F1 group when compared to CTL-DH-F1 group. CHOL and TG fasting serum levels were similar between CTL-DP-F1 and GF-DP-F1 and significantly lower to CTL DH-F1. Liver weight were higher in GF-DP-F1 group when compared to CTL DP-F1. Stands out that liver weight in GF-DH-F1 were higher in relation to CTL DH-F1. Liver total lipids content was similar between CTL-DP-FQ and GF-DP F1, but the TG content was higher in GF-DP-F1 group. GF-DH-F1 shows liver total lipids content and TG lower in relation to GF-DP-F1. The groups that received high-fat diet showed steatosis on liver. It was observed fibrosis on liver of 66.67% in CTL-DH-F1 and 40% in GF-DH-F1. All the treatment groups had lobular inflammation. Thus, it was show for the first time that maternal exposure to glyphosate in male mice leads to hepatic inflammation on adult offspring. When we analyzed the offspring which received high-fat diet, we observed that puppies which mothers were exposed to glyphosate had fat pad accumulation on white adipose tissue and liver, as well as soft dyslipidemia in relation to control dams offspring which received high-fat-diet.